Multiple Domains of Fission Yeast Cdc19p (MCM2) Are Required for Its Association with the Core MCM Complex - Sherman, Daniel A. (The American Society for Cell Biology, 1998)
The members of the MCM protein family are essential eukaryotic DNA replication factors that form a six-member protein complex. In this study, we use antibodies to four MCM proteins to investigate the structure of and requirements for the formation of fission yeast MCM complexes in vivo, with particular regard to Cdc19p (MCM2). Gel filtration analysis shows that the MCM protein complexes are unstable and can be broken down to subcomplexes. Using coimmunoprecipitation, we find that Mis5p (MCM6) and Cdc21p (MCM4) are tightly associated with one another in a core complex with which Cdc19p loosely associates. Assembly of Cdc19p with the core depends upon Cdc21p. Interestingly, there is no obvious change in Cdc19p-containing MCM complexes through the cell cycle. Using a panel of Cdc19p mutants, we find that multiple domains of Cdc19p are required for MCM binding. These studies indicate that MCM complexes in fission yeast have distinct substructures, which may be relevant for function.